Internacionalización de las pymes: barreras y estrategias. - Calle Aguilar, Jocelyne Estefania (My University, 2020)
The present work called the internationalization of SMEs: barriers and strategies, was prepared in order to identify international marketing strategies focused on SMEs to insert their products in the foreign market. For its preparation, the qualitative research methodology based on a literature review of sources obtained in scientific articles was applied. Within the research, it was possible to verify the internal and external barriers that SMEs face when internationalizing, giving greater emphasis to barriers such as: lack of information and lack of financing. For this reason, the most suitable strategies that have been taken into account are strategic alliances and the innovation strategy, since these allow us to minimize the risk that entrepreneurs do not fulfill the objective of internationalizing their company.
El presente trabajo denominado internacionalización de las pymes: barreras y estrategias, se elaboró con la finalidad identificar las estrategias de marketing internacional enfocadas en las pymes para insertar sus productos en el mercado extranjero. Para su elaboración se procedió aplicar la metodología de investigación cualitativa basada en revisión de literatura de fuentes obtenidas en artículos científicos. Dentro de la investigación, se pudo constatar las barreras internas y externas que enfrentan las pymes al momento de internacionalizarse, dando un realce mayor a las barreras como: la falta de información y la falta de financiamiento. Por esta razón las estrategias más idóneas que se han tomado en cuenta son las alianzas estratégicas y la estrategia de innovación ya que estas permiten minimizar el riesgo de que los empresarios no cumplan con el objetivo de internacionalizar su empresa.
Keywords: MARKETING INTERNACIONAL; PYMES; BARRERAS; ESTRATEGIAS